Computational and experimental approach to evaluate the effect of initiator concentration, solvents, and enes on the TEMPO driven thiol–ene reaction. (23rd October 2020) - Hafeez, Sumbul; Khatri, Vikas; Kashyap, Hemant K.; Nebhani, Leena
Abstract : The fundamental mechanism and reaction kinetics of the TEMPO initiated thiol–ene reaction between benzyl mercaptan and variable enes in the presence of varying initiator concentration and varying solvents has been studied experimentally and computationally. Abstract : The fundamental mechanism and reaction kinetics of the TEMPO ((2, 2, 6, 6-tetramethyl piperidin-1-yl)oxyl) initiated thiol–ene reaction between benzyl mercaptan and variable enes (divinyl sulfone, n -butyl acrylate, N, N -dimethylacrylamide, vinyltriethoxysilane and 1-dodecene), in the presence of varying initiator concentrations (0, 0.01, 0.05, 0.08 and 0.1 mmol) and varying solvents (methanol, tetrahydrofuran and chloroform) has been studied experimentally and computationally. The DFT (density functional theory) calculations have been used to investigate the effect of variable enes on the thiol–ene reaction. From the computational and experimental results, it can be concluded that the varying initiator concentrations, varying solvents and nature of enes directly influence the TEMPO initiated thiol–ene reaction. For the TEMPO initiated thiol–ene reaction, electron-deficient enes, such as divinyl sulfone, and n -butyl acrylate, exhibited quantitative conversion in 8 h using methanol as a solvent at 35 °C, however electron-rich ene, such as vinyltriethoxysilane, showed no thioether formation and 1-dodecene showed 30% conversion in 8 h using methanol as a solvent at 35 °C. The reaction between benzyl mercaptan and electron deficient enes, such as divinyl sulfone, n -butyl acrylate and N, N -dimethylacrylamide, exhibited quantitative conversion in 16 h using chloroform and tetrahydrofuran as solvent at 35 °C. All the experimental studies were monitored via 1 H NMR spectroscopy. Additionally, the reactivity of ene toward the thiol–ene reaction was also determined using DFT calculations, which was found to be in agreement with the experimental data. Methanol as a solvent exhibited higher reactivity towards the TEMPO initiated thiol–ene reaction as compared to tetrahydrofuran and chloroform, which was demonstrated by the solvation model based on density (SMD).